Exploiting the fundamentals of biological organization for the advancement of biofabrication. (April 2022) - Hill, Jordan; Wildman, Ricky; Mata, Alvaro
Graphical abstract: Highlights: Recent developments in biofabrication are reviewed. Biological organization principles (BOPs) offer alternatives in biofabrication. Advancements in scalability, reproducibility, and biomimicry are presented. Remaining challenges are discussed as well as the future scope of the field. Abstract : The field of biofabrication continues to progress, offering higher levels of spatial control, reproducibility, and functionality. However, we remain far from recapitulating what nature has achieved. Biological systems such as tissues and organs are assembled from the bottom-up through coordinated supramolecular and cellular processes that result in their remarkable structures and functionalities. In this perspective, we propose that incorporating such biological assembling mechanisms within fabrication techniques, offers an opportunity to push the boundaries of biofabrication. We dissect these mechanisms into distinct biological organization principles (BOPs) including self-assembly, compartmentalization, diffusion-reaction, disorder-to-order transitions, and out-of-equilibrium processes. We highlight recent work demonstrating the viability and potential of these approaches to enhance scalability, reproducibility, vascularization, and biomimicry; as well as current challenges to overcome.